Insecticidal Activity of Extracts of Aglaia spp. (Meliaceae) against Cabbage Cluster Caterpillar Crocidolomia binotalis Zeller (Lepidoptera: Pyralidae) - Djoko Prijono; Partomuan Simanjuntak; Bambang W. Nugroho; Sudarmo Sudarmo; Shinta Puspitasari (Universitas Gadjah Mada, 2001)
Insecticidal potential of eleven species of Aglaia (Meliaceae) was evaluated in the laboratory against the cabbage cluster caterpillar, Crocidolomia binotalis. The feeding treatment of second-instar larvae C. binotalis for 48 hours with ethanol twig extract of A. odorata at 0.5% caused 98.7% larval mortality; leaf and twig extracts of A. elaeagnoidea caused 17.3% and 6.7% mortality, respectively; twig extracts of A. argentea, A. formosana, and A. latifolia caused only 1.3% mortality each; whereas extracts of the other six Aglaia species were inactive (0% mortality). Further tests with A. odorata showed that twigs gave the most active extract compared to other plant parts (leaves, flowers, and roots), and air-drying of plant materials for 2 weeks markedly decreased the activity of the derived extracts. The active extracts also delayed the development of surviving larvae in similar degree to the level of their lethal effect. LC50 of ethyl acetate fraction of A. odorata twig extract and its main active compound, rocaglamide, against C. binotalis larvae were 310.2 and 31.4 ppm, respectively. This active compound was about 8.7 times less potent than azadirachtin (LC50 3.6 ppm).